Cyberattacks and Cybersecurity: Concepts, Current Challenges, and Future Research Directions - Ţălu, Mircea (Digital Technologies Research and Applications, 2025)
Cyberspace is the foundation of modern economic, social, and governmental activities, making cybersecurity an essential component in addressing the escalating threat of cyberattacks. These attacks, which exploit vulnerabilities through methods such as malware, data breaches, and Distributed Denial of Service attacks, lead to significant disruptions ranging from financial losses for businesses to political and military consequences. As the digital landscape evolves, the need for robust cybersecurity measures to protect interconnected systems and safeguard digital ecosystems becomes increasingly urgent. This paper provides a review of the foundational concepts of cybersecurity, offering an in-depth analysis of current challenges and strategies. Furthermore, by critically assessing the weaknesses in existing methods, this study identifies knowledge gaps and proposes actionable future research directions aimed at mitigating cyber threats.